Role of phosphorylation of Thr17 residue of phospholamban in mechanical recovery during hypercapnic acidosis - Mundiña-Weilenmann, Cecilia (2005)
Objectives: To assess the time course of phosphorylation of phospholamban residues, the underlying mechanisms determining these phosphorylations, and their functional impact on the mechanical recovery during acidosis. Methods: Langendorff perfused rat hearts were submitted to 30 min of hypercapnic acidosis. Contractility, relaxation, and phosphorylation of phospholamban residues, immunodetected by specific antibodies, were determined. Results: Acidosis produced a mechanical impairment followed by a spontaneous recovery, most of which occurred within the first 3 min of acidosis (early recovery). During this period, contractility and relaxation recovered by 67±9% and 77±11%, respectively, from its maximal depression, together with an increase in the Ca2+-calmodulin-dependent protein kinase II (CaMKII)-dependent phosphorylation of Thr17. The CaMKII inhibitor KN-93, at 1, 5 and 10 μM, decreased Thr17 phosphorylation to basal levels and produced a similar impairment of the early relaxation recovery (50%). However, only 5 and 10 μM KN-93 inhibited the early contractile recovery and completely blunted the late mechanical recovery. Inhibition of the reverse mode of the Na+/Ca2+ exchanger by KB-R7943 decreased Thr17 phosphorylation but accelerated the early contractile recovery. Conclusions: CaMKII-dependent Thr17 phosphorylation significantly increased at the beginning of acidosis, is responsible for 50% of the early relaxation recovery, and is linked to the activation of the reverse Na+/Ca2+ mode. The early contractile recovery and the late mechanical recovery are dependent on CaMKII but independent of the phosphorylation of the Thr17 residue of phospholamban. The reverse Na+/Ca2+ mode has an additional negative effect that opposes the early mechanical recovery.